The Use of Animation-Based Fairy Tales Media to Improve the Listening Skills of Elementary Schools Students - Fitriyana, Nofia; Hasanudin, Cahyo (Proceedings International Conference on Education Innovation and Social Science, 2022)
This study aims to find out how animation-based fairy tale media can play a role in improving listening skills in elementary school children. The method in this study uses the literature study method with secondary data sources originating from national and international journals and books. The procedure in this study uses the theory of Mary W. George which has been developed. The results of the research are discussion topics that focus on the role of collaboration between fairy tales and animation media to improve skills. Collaboration between fairy tales and animation can be done by developing and designing fairy tale scripts that have been written so that they can be delivered with animated media.